Systematic Review: How the Reading Aloud Strategy Still Used in the Last Five Years - Nirwana, Iin; Mahmudah, Khotimah; Pratama, Aryawira (SALEE: Study of Applied Linguistics and English Education, 2025)
The main objective of this study is to explore a study of Reading Aloud Strategy in Teaching English as a Foreign Language (EFL) and its relevance in contemporary educational settings. This research specifically addresses the following objectives: to identify the implications of RA implementation, determine the most effective strategies for its application, and evaluate its effectiveness across different educational levels. Data in the form of articles retrieved through internet search engines at the last five years; between 2018 and 2022. Key search terms included "Reading Aloud," "EFL reading strategies," and "teaching reading comprehension." Articles were selected based on criteria such as publication type, accessibility, participant demographics, research methods, and their focus on RA in EFL contexts. Findings are categorized based on their contributions to answering the research questions, providing insights into the strategic implementation and outcomes of RA in various educational settings. The result reveals that the RA strategy continues to be a adaptable and valuable strategy in Teaching English. Educators are still encouraged to adapt RA methods to their specific classroom contexts, using both traditional and technological approaches to maximize student outcomes in reading comprehension and other learning objectives.